DEOLOGI PATRIARKI DALAM IKLAN AXE EFFECT ‘CALL ME’ VERSI SPECIAL NEEDS DAN LOST - Ercilia Rini Octavia (Gelar : Jurnal Seni Budaya, 2014)
The advertisement through its sign and code brings a certain meaning that is personally interpreted by theaudience based on their own cultural experiences. As a text, advertisement which is shown in a set of signand code from the addresser to the addressee expresses the ideological practice. The act of reading televisionadvertisement can be meant as an effort to convey the ideological practice working manipulatively in a certainsocial condition. Axe with the advertisement series Axe Effect Call Me especially Special Needs and Lostversion carries the ideology of patriarchy. Patriarchy is all forms of man mastery /upon/over/towards woman.The man superiority towards woman is presented in a story and visual performance that exploits the appeal ofwoman sensuality.Keywords: Axe, semiotics, sensuality, advertisement, ideology